JURNALISME SASTRA: LAPORAN PERISTIWA SECARA NARATIF DAN VARIATIF - Suhaimi Suhaimi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
Internet as a form of communication technology today, on the onehand has urged members of the press who worked on several major news papers to changeform into smaller, but the number of pages grew thicker with amore slender appearance and full color. It is achallenge for reporters now are required tobe more skilled from their elders in preparing the report journalism.Literary journalism or narrative reporting is news writing made in narra-tiveform of variety of different angles according to the facts and not fiction essay. InIndonesia literary journalism gives a place for journalists to actualize hisbeing. Therefore, it requires a journalist to be able to create a narrative,descriptive or a detailed, lively, contextual, and relevant reports